The Cost-Effectiveness of Colonic Stenting as a Bridge to Curative Surgery in Patients with Acute Left-Sided Malignant Colonic Obstruction: A Canadian Perspective - Harminder Singh; Steven Latosinsky; Brennan MR Spiegel; Laura E Targownik (Canadian Journal of Gastroenterology)
BACKGROUND: Over the past several years, colonic stenting has been advocated as an alternative to the traditional surgical approach for relieving acute malignant left-sided colonic obstruction. The aim of the present study was to determine the most cost-effective strategy in a Canadian setting.